Beban pekerjaan, tingkat stres dan komitmen organisasi terhadap niat auditor resign - Yantomi Yantomi (LPMP Imperium, 2024)
This study investigates the impact of workload, organizational commitment, and stress levels on auditors' intention to resign. The study utilizes quantitative methods and primary data obtained through an online survey using a questionnaire on Google Forms. The survey was distributed to individuals with work experience at KAPs in DKI Jakarta and West Java, excluding Big Four KAPs aged between 20 and 60 years with at least two years of experience. The findings indicate that workload does not directly affect auditors' intention to resign. At the same time, organizational commitment and stress levels significantly impact the organization. Additionally, when considered together, workload, organizational commitment, and stress levels collectively influence auditors' intention to resign. Public interest statements The research's findings can improve the public's understanding of the importance of transparency and accountability in accounting practices. It can also provide practical guidance for non-Big Four accounting firms in DKI Jakarta and West Java, improving efficiency and effectiveness in their services. .